Association of cigarette smoking with radial augmentation index: the Circulatory Risk in Communities Study (CIRCS). Issue 12 (December 2018) - Li, Jiaqi; Cui, Renzhe; Eshak, Ehab; Yamagishi, Kazumasa; Imano, Hironori; Muraki, Isao; Hayama-Terada, Mina; Kiyama, Masahiko; Okada, Takeo; Iso, Hiroyasu
Abstract This study aimed to assess the association of cigarette smoking with radial augmentation index among the Asian general population. We conducted a cross-sectional population-based study including 1593 men and 2671 women aged 40–79 years. Smoking status was ascertained through interviews, and the number of pack-years was calculated. The radial augmentation index was defined as the ratio of central pulse pressure to brachial pulse pressure, as measured using an automated tonometer: the HEM-9000AI (Omron Healthcare co., Kyoto, Japan). There was a higher prevalence of an increased radial augmentation index among current male smokers who smoked ≥ 30 cigarettes/day and all female smokers than among never smokers. After adjusting for known risk factors of atherosclerosis, the multivariable odds ratio (OR) [95% confidence interval (CI)] for a high radial augmentation index for current male smokers who smoked ≥30 cigarettes/day compared with never smokers was 1.9 (1.1–3.4). The multivariable OR (95% CI) for a high radial augmentation index for former female smokers and current female smokers compared with never smokers was 1.8 (1.2–2.7) and 2.5 (1.6–3.9), respectively. Moreover, smoking pack-years was positively associated with a high radial augmentation index in both sexes. There were no relationship between smoking status and high central or brachial pulse pressures among subjects of either sex. In conclusion, cigarette smoking and cumulative smoking exposure were positively associated with an increased radial augmentation index in men who smoked heavily and in women.